1999
DOI: 10.1016/s0378-1097(99)00434-6
|View full text |Cite
|
Sign up to set email alerts
|

The induction of sporulation in the aquatic fungus Blastocladiella emersonii is dependent on extracellular calcium

Abstract: Induction of sporulation in Blastocladiella emersonii is absolutely dependent on extracellular calcium. Vegetative cells grown in media with or without calcium do not sporulate in media devoid of calcium or in CaCl 2 with EGTA. Calcium channel blockers, CoCl 2 and nifedipine, and ionophore A23187 inhibited the induction of sporulation. The calmodulin antagonists trifluoperazine and chlorpromazine inhibited the sporulation when present in the cultures at least 60 min after induction. So, calcium that is accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
11
0
4
Order By: Relevance
“…Due to the fact that B. emersonii sporulation is totally dependent on extracellular Ca 2+ (Coutinho and Correa, 1999), and that some nitric oxide synthases (NOS), such as the mammalian constitutive NOS, are activated by elevated intracellular Ca 2+ levels (Alderton et al, 2001;Wendehenne et al, 2001), the effect of EGTA on the putative nitric oxide synthase activity was investigated. First, the results obtained by (Coutinho and Correa, 1999) concerning the rapid Ca 2+ uptake during the initial 10 min of sporulation were reproduced by confocal laser-scanning microscopy using the Ca 2+ fluorescent indicator Fluo3 (Fig.…”
Section: A Putative Nitric Oxide Synthase Activity Is Present In B Ementioning
confidence: 99%
See 2 more Smart Citations
“…Due to the fact that B. emersonii sporulation is totally dependent on extracellular Ca 2+ (Coutinho and Correa, 1999), and that some nitric oxide synthases (NOS), such as the mammalian constitutive NOS, are activated by elevated intracellular Ca 2+ levels (Alderton et al, 2001;Wendehenne et al, 2001), the effect of EGTA on the putative nitric oxide synthase activity was investigated. First, the results obtained by (Coutinho and Correa, 1999) concerning the rapid Ca 2+ uptake during the initial 10 min of sporulation were reproduced by confocal laser-scanning microscopy using the Ca 2+ fluorescent indicator Fluo3 (Fig.…”
Section: A Putative Nitric Oxide Synthase Activity Is Present In B Ementioning
confidence: 99%
“…emersonii sporulation is entirely dependent on extracellular calcium, as it was observed that vegetative cells grown in medium with or without calcium do not sporulate in the absence of calcium or in the presence of CaCl 2 and EGTA (Coutinho and Correa, 1999). In addition, experiments using the calmodulin antagonists, trifluoperazine, and chlorpromazine, suggested that early events in sporulation are dependent on calcium and calmodulin-like functions (Coutinho and Correa, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lanthanum, which blocks the uptake and efflux of Ca 2ϩ , inhibits germination completely when added at the time of induction (8). Calcium was also found to be both necessary and sufficient for sporulation of B. emersonii, and low levels of Ca 2ϩ were observed to enhance the stability of zoospores (2,35,36). Calmodulin (CaM), a small acidic protein whose primary role is to serve as an intracellular Ca 2ϩ receptor modulating the activity of numerous intracellular proteins involved in diverse signaling pathways (49), is found in B. emersonii zoospores (7,33).…”
mentioning
confidence: 99%
“…In the laboratory, sporulation can be triggered by washing and resuspension of the cells in a buffered solution containing 1 mM Ca 2ϩ . In fact, both calcium and the calcium-binding protein calmodulin have been shown to be necessary at the earliest stages of this process (4,33,34). Under starvation conditions, cells undergo an ordered and synchronized sequence of morphological and physiological changes.…”
mentioning
confidence: 99%